Abdominal actinomycosis mimicking ruptured appendicitis/appendiceal tumor in a 4-year-old female: A case report with resolution using minimal antibiotics - Ruby Lopez-Flores; Jennifer Reifsnyder; Margo Hendrickson (Elsevier, 2023)
Actinomycosis is a rare infection with Actinomyces israelii mostly seen in the craniofacial region in post pubertal individuals. We present the youngest case of abdominal actinomycosis in a 4-year-old female. Her initial presentation led to a diagnosis consistent with ruptured appendicitis with abscess on computed tomography (CT) imaging. Surgical exploration revealed a firm mass involving the cecum, appendix, sigmoid colon and bladder dome suggestive of a soft tissue tumor on frozen section. Final histologic analysis indicated abdominal actinomycosis in the cecum and sigmoid colon with no evidence of a neoplastic process. With source control, this patient did well with a very short course of antibiotics.